The trends in antibiotic use by general dental practitioners in the Czech Republic (2006–2012). (11th January 2014) - Pipalova, Rachel; Vlcek, Jiri; Slezak, Radovan
<x xml:space="preserve">Abstract</x> We assessed antibiotic prescribing in practical dentistry in the Czech Republic, as antibiotics are widely prescribed by dental practitioners and warning signals of their overuse can be observed. The individual antibiotic prescriptions were extracted from the database of the General Health Insurance Company and further analysed. The proportion of dentists' prescription within the whole primary health‐care sector and the rate of prescriptions of particular antibiotics were both in defined daily doses per 1, 000 insurees and day (DID) and in number of prescriptions calculated. The proportion of antibiotic use in dentistry increased from 0.63 DID in 2006 to 0.75 DID. We found a decline in use of narrow‐spectrum penicillins by 4.8%, tetracyclines by 3.5% and macrolides by 3.6%, accompanied by increasing rate of prescription of aminopenicillins combined with beta‐lactamase inhibitor by 8.9% and lincosamides by 8.5%. The consumption of clindamycin and amoxicillin combined with clavulanate in DID has increased by approximately 60% since 2006 thanks to the exclusive prescribing of two commercial oral products only. Factors contributing to this unfavourable trend are commercial influence or defensive medicine practice.